Statins reduce mortality in patients with COVID-19: an updated meta-analysis of 147 824 patients - Diaz-Arocutipa, Carlos (2021)
Objectives: There is conflicting evidence about the efficacy of statin use in regard to clinical outcomes in patients with coronavirus disease 2019 (COVID-19). A systematic review and meta-analysis was performed to examine the effect of statin use on mortality in COVID-19 patients. Methods: The electronic databases were searched, from inception to March 3, 2021. Unadjusted and adjusted effect estimates with their 95% confidence intervals (95% CI) were pooled using random-effects models. Results: Twenty-five cohort studies involving 147 824 patients were included. The mean age of the patients ranged from 44.9 to 70.9 years; 57% of patients were male and 43% were female. The use of statins was not associated with mortality when applying the unadjusted risk ratio (uRR 1.16, 95% CI 0.86–1.57; 19 studies). In contrast, meta-analyses of the adjusted odds ratio (aOR 0.67, 95% CI 0.52–0.86; 11 studies) and adjusted hazard ratio (aHR 0.73, 95% CI 0.58–0.91; 10 studies) showed that statins were independently associated with a significant reduction in mortality. Subgroup analyses showed that only chronic use of statins significantly reduced mortality according to the adjusted models. Conclusions: The use of statins was found to be associated with a lower risk of mortality in COVID-19 patients based on adjusted effects of cohort studies. However, randomized controlled trials are still needed to confirm these findings.